Silk fibroin microparticle scaffold for use in bone void filling: safety and efficacy studies - Deshpande, Rucha; Shukla, Swati; Kale, Amod; Deshmukh, Narendra; Nisal, Anuya; Venugopalan, Premnath (ACS Biomaterials Science & Engineering, 2022)
Silk fibroin (SF) is a natural biocompatible protein polymer extracted from cocoons of silkworm Bombyx mori. SF can be processed into a variety of different forms and shapes that can be used as scaffolds to support bone regeneration. Threedimensional (3D) SF scaffolds have shown promise in bone-void -filling applications. In in vitro studies, it has been demonstrated that a microparticle-based SF (M-RSF) scaffold promotes the differentiation of stem cells into an osteoblastic lineage. The expression of differentiation markers was also significantly higher for M-RSF scaffolds as compared to other SF scaffolds and commercial ceramic scaffolds. In this work, we have evaluated the in vitro and in vivo biocompatibility of M-RSF scaffolds as per the ISO 10993 guidelines in a Good Laboratory Practice (GLP)-certified facility. The cytotoxicity, immunogenicity, genotoxicity, systemic toxicity, and implantation studies confirmed that the M-RSF scaffold is biocompatible. Further, the performance of the MRSF scaffold to support bone formation was evaluated in in vivo bone implantation studies in a rabbit model. Calcium sulfate (CaSO4) scaffolds were chosen as reference material for this study as they are one of the preferred materials for bone-void -filling applications. M-RSF scaffold implantation sites showed a higher number of osteoblast and osteoclast cells as compared to CaSO4 implantation sites indicating active bone remodeling. The number density of osteocytes was double for M-RSF scaffold implantation sites, and these M-RSF scaffold implantation sites were characterized by enhanced collagen deposition, pointing toward a finer quality of the new bone formed. Moreover, the M-RSF scaffold implantation sites had a negligible incidence of secondary fractures as compared to the CaSO4 implantation sites (similar to 50% sites with secondary fracture), implying a reduction in postsurgical complications. Thus, the study demonstrates that the M-RSF scaffold is nontoxic for bone-void -filling applications and facilitates superior healing of fracture defects as compared to commercial calcium-based bone void fillers.
Keywords: Biocompatibility; biological safety; bone void filler; ISO 10993; M-RSF; Serioss; Silk fibroin

Engineered silk matrix as a substitute for acellular dermal matrix in breast reconstruction surgery - Deshpande, Rucha; Shukla, Swati; Kale, Amod; Sayyad, Raeesa; Kewale, Bhawana; Deshmukh, Narendra; Nisal, Anuya; Venugopalan, Premnath (International Journal of Biological Macromolecules, 2025)
Implant-based breast reconstruction is a common standard of care for breast cancer patients following mastectomy. To support implant weight and placement, surgeons utilize autologous tissues, acellular dermal matrices (ADMs), or synthetic meshes. While ADMs provide structural support, they present significant risks, including infection transmission and seroma. Conversely, synthetic meshes exhibit poor cellular adhesion, leading to inadequate tissue integration. To address these challenges, there is a need for a matrix that enhances tissue integration while minimizing infection risks and other complications. Silk fibroin (SF), a natural biopolymer, possesses excellent biocompatibility and mechanical properties. This study introduces a novel engineered silk matrix (ESM) as an advanced solution for soft tissue regeneration, specifically in breast reconstruction surgery. The present study establishes the safety of ESM and evaluates its potential a tissue regeneration matrix through extensive in-vitro and in-vivo analyses. In-vitro assays demonstrated superior cellular adhesion, proliferation of human mammary fibroblast cells (HMFCs), collagen deposition and angiogenesis in ESM compared to collagen matrices and ADMs. Safety assessments, conducted in accordance with ISO 10993 guidelines, confirmed noncytotoxic nature of ESM. Furthermore, subcutaneous implantation revealed no systemic toxicity or adverse tissue reactions. In-vivo studies utilizing a Yorkshire pig model of simulated breast reconstruction surgery, demonstrated superior performance of ESM over collagen matrices in tissue regeneration. The findings showed enhanced fibroblast density, increased collagen deposition, and improved vascularization. These results suggest that ESM is a safer and more effective alternative to ADMs in breast reconstruction, with the potential to revolutionize post-mastectomy care for breast cancer patients.
Keywords: Biocompatibility; Breast reconstruction; ISO 10993; Polymer; Safety; Silk protein; tissue regeneration